PENGARUH KEPUTUSAN INVESTASI, KEPUTUSAN PENDANAAN, KEBIJAKAN DIVIDEN, KEPEMILIKAN MANAJERIAL, DAN KEPEMILIKAN INSTITUSIONAL TERHADAP NILAI PERUSAHAAN (Studi Empiris pada Perusahaan yang Terdaftar di Bursa Efek Indonesia Tahun 2011-2012) - Ratnasari Kusumaningrum, Dyah Ayu; Nur Rahardjo, Shiddiq (Diponegoro Journal of Accounting, 2013)
The purpose of this study is to analyze the impact of investment decision, financing decision, dividend policy, managerial ownership, and institutional ownership to the firm value. The population in this study are all of the companies listed on the Indonesia Stock Exchange and is continously published the annual report in the year 2011-2012. The sample obtained was 132 observations using purposive sampling method. This study used multiple linear regression as a data analysis tool. The result of this research showed that investment decision and dividend policy have a positive impact to the firm value. Whereas financing decision, managerial ownership, and institutional ownership have a negative impact to the firm value.